Novel identity-based fully homomorphic encryption scheme from lattice - Yong-li TANG; Ming-xing HU; Kun LIU; Qing YE; Xi-xi YAN (Tongxin xuebao)
The previous identity-based homomorphic encryption schemes from lattice was analyzed.That the high complexity in previous schemes was mainly caused by trapdoor generation and preimage sampling was pointed out.A new solution was proposed.A novel identity-based encryption scheme from lattice by combining new trapdoor function and dual-LWE algorithm organically was constructed,and it was transformed to an identity-based fully homomorphic encryption scheme from lattice by employing the idea of eigenvector.Comparative analysis shows that the scheme’s complexity of trapdoor generation has a significant reduction,the complexity of preimage sampling has a nearly three-fold reduction,and the SIVP approximation factor has a <msqrt> m </msqrt> times reduction.The security of the proposed scheme strictly reduces to the hardness of decisional learning with errors problem in the standard model.